Pengaruh Implementasi Kebijakan Proteksionisme Melalui Tingkat Komponen Dalam Negeri Terhadap Tender/Seleksi Internasional - Alif Duta Hardenta; Shafira Dinda Ariefti; Wiweko Rahadian Abyapta (Fakultas Hukum Universitas Islam Indonesia, 2023)
The policy of protectionism has been adopted by a number of countries including Indonesia with the aim of protecting and improving the quality of domestic products. One form of the protectionism policy is through the Local Content Requirement which is realized by the Domestic Component Level (TKDN) policy. This policy affects the implementation of international selection process process (popularly known as ‘tenders’) which are a special form of government procurement of goods/services. This procurement is guaranteed by regulations due to the involvement of foreign parties in the selection process which can determine the outcome of the procurement. This research departs from the problem of international trade protectionism policies and the influence of TKDN policies in the regulations of the government procurement of goods/services which governs the international selection process. The research method used is normative juridical along with non-interactive qualitative. The results of the research conclude that the protectionism policy adopted by Indonesia encourages TKDN obligations in the procurement of government goods/services as one of the considerations to become one of the determining factors in the passage of international selection. This policy creates space for the use of domestic products to be applied in the process of government procurement of goods/services. Nonetheless, the TKDN policy on the one hand impedes the smooth running of the international selection process by limiting potential foreign participants in the international procurement mechanism. In addition, this research also concludes that in practice through cases there are conflicts with obligations regarding TKDN which are not fully considered in government goods/services procurement activities.Key Words: Government procurement of goods and/or services; international selection/tender; Domestic Component Level; Local Content Requirement; protectionism policy AbstrakKebijakan proteksionisme diambil oleh sejumlah negara seperti Indonesia dengan tujuan melindungi dan meningkatkan kualitas produk dalam negeri. Salah satu bentuk dari kebijakan proteksionisme ini adalah melalui Local Content Requirement yang diwujudkan dengan kebijakan Tingkat Komponen Dalam Negeri (TKDN). Kebijakan ini mempengaruhi penyelenggaraan seleksi/tender internasional yang merupakan salah satu bentuk khusus pengadaan barang/jasa pemerintah. Pengadaan ini dijamin oleh regulasi dikarenakan adanya keterlibatan pihak asing dalam seleksi/tender yang dapat menentukan hasil pengadaan. Penelitian ini berangkat dari permasalahan kebijakan proteksionisme perdagangan internasional dan pengaruh kebijakan TKDN pada peraturan pengadaan barang/jasa pemerintah yang mengatur proses seleksi/tender internasional. Metode penelitian yang digunakan adalah yuridis normatif beserta kualitatif non-interaktif. Hasil penelitian menyimpulkan bahwa kebijakan proteksionisme yang dianut oleh Indonesia mendorong adanya kewajiban TKDN dalam pengadaan barang/jasa pemerintah sebagai salah satu pertimbangan untuk menjadi salah satu faktor penentu dalam berjalannya seleksi/tender internasional. Kebijakan tersebut menciptakan ruang bagi penggunaan produk dalam negeri untuk diterapkan pada proses pengadaan barang/jasa pemerintah. Meskipun demikian kebijakan TKDN pada satu sisi menghambat kelancaran proses seleksi/tender internasional dengan membatasi calon peserta asing dalam mekanisme pengadaan internasional. Selain itu penelitian ini juga menyimpulkan bahwa dalam praktiknya melalui kasus terdapat pertentangan terhadap kewajiban tentang TKDN yang tidak sepenuhnya dipertimbangkan dalam kegiatan pengadaan barang/jasa pemerintah. Kata-kata Kunci: Pengadaan barang dan/atau jasa pemerintah; seleksi/tender internasional; Tingkat Komponen Dalam Negeri; Local Content Requirement; kebijakan proteksionisme